2012
DOI: 10.4071/isom-2012-wp21
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Aging Effects on the Thermal reliability Performance of Lead-Free Solder Joints

Abstract: Recently, an intermittent hot-pressing process had been developed and applied to produce bamboo bundle laminated veneer lumber (BLVL) joints with lengths of more than 6 m. According to our previous studies, there was a major difference in the physical and mechanical performance of hot-pressing joints and at adjacent positions on the lumber. In this paper, heat transfer and the effects of various aging temperatures on the mechanical performance of the joints of intermittent hot-pressed BLVLs were studied. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Motalab, et al [11][12][13] have included aging effects in the Anand constitutive model and energy density based failure criterion for SAC solders, and then used these theories with finite element analyses to predict the thermal cycling life of aged BGA assemblies. Good correlations were achieved with the measured lifetimes from references [9][10]. Finally, Lall, et al have studied the high strain rate behavior of SAC solders subjected to aging [14].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Motalab, et al [11][12][13] have included aging effects in the Anand constitutive model and energy density based failure criterion for SAC solders, and then used these theories with finite element analyses to predict the thermal cycling life of aged BGA assemblies. Good correlations were achieved with the measured lifetimes from references [9][10]. Finally, Lall, et al have studied the high strain rate behavior of SAC solders subjected to aging [14].…”
Section: Introductionmentioning
confidence: 66%
“…Aging effects on the constitutive and failure behaviors of lead free solders have been studied extensively by the authors and their coworkers [2][3][4][5][6][7][8][9][10][11][12][13][14]. In early investigations, the mechanical properties and creep behavior of SAC alloys were shown to be severely degraded by prior exposure to room temperature (25 C) and elevated temperature (50, 75, 100, and 125 C) aging [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table I summarizes the characteristic life (η from Weibull plot) and provides a comparison between packages. In general, Pb-free solder with ENIG and ENEPIG outperform ImAg under identical test conditions; in addition, the SAC305 solder alloy performs better than SAC105 in all test groups, which compares favorably with [4]- [7]. The characteristic life for no aging 10-mm SAC105 solder on ImAg, ENIG, and ENEPIG were 2419, 3422, and 3536 cycles, respectively.…”
Section: A Accelerated Temperature Cycling Data Analysismentioning
confidence: 98%
“…Only limited attention has been paid to the effect of package characteristic lifetime reliability during long-term isothermal aging at elevated temperatures, which is the focus of this paper. Zhang et al [4]- [8] and Hai et al [9] concluded that a drastic reduction on packaging reliability occurs during isothermal aging for fine-pitch ball grid array (BGA) packages with Sn-1.0Ag-0.5Cu (SAC105), Sn-3.0Ag-0.5Cu (SAC305), and Sn-37Pb solder ball interconnects. The trends were in the expected directions; namely, the reliability was reduced when using higher aging temperatures, smaller solder balls, and lower Ag-content alloy, since creep deformation is known to operate principally on grain and/or phase boundaries.…”
Section: Introductionmentioning
confidence: 99%